2021
DOI: 10.1093/ijnp/pyab041
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Learning From Negative Feedback in Stimulant Use Disorder: Dopaminergic Modulation

Abstract: Background Drug-induced alterations to the dopamine system in stimulant use disorder (SUD) are hypothesised to impair reinforcement learning. Computational modelling enables the investigation of the latent processes of reinforcement learning in SUD patients, which could elucidate the nature of their impairments. Methods We investigated reinforcement learning in 44 SUD patients and 41 healthy control participants using a proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 97 publications
3
25
1
Order By: Relevance
“…However, other studies in humans [75,76] and in animals [77][78][79][80] pointed to the specific role of dopamine D 2 receptors in avoiding negative outcomes [73,81]. A recent study by Lim and collaborators [82] confirmed the blunting effects of dopamine D 2 receptor agonism on learning from negative feedback in healthy participants and reported similar effects on learning from punishment, following the administration of the dopamine D 2/3 receptor antagonist amisulpride. Such a nonselective effect of dopamine D 2/3 receptor antagonism has already been previously reported [83,84], suggesting that these receptors are generally involved in feedback-based learning.…”
Section: Biased Sensitivity To Feedbackmentioning
confidence: 97%
“…However, other studies in humans [75,76] and in animals [77][78][79][80] pointed to the specific role of dopamine D 2 receptors in avoiding negative outcomes [73,81]. A recent study by Lim and collaborators [82] confirmed the blunting effects of dopamine D 2 receptor agonism on learning from negative feedback in healthy participants and reported similar effects on learning from punishment, following the administration of the dopamine D 2/3 receptor antagonist amisulpride. Such a nonselective effect of dopamine D 2/3 receptor antagonism has already been previously reported [83,84], suggesting that these receptors are generally involved in feedback-based learning.…”
Section: Biased Sensitivity To Feedbackmentioning
confidence: 97%
“…Substance use disorders (SUDs) are associated with loss of control over drug-taking behavior regardless of its negative consequences (R. Smith et al, 2020). Methamphetamine is considered as one of the most widely prevalent illegal narcotics in the world and chronic use of it can alter the feedback processing system of the brain (Lim et al, 2021;R. Smith et al, 2020;Wei et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al, 2020). Methamphetamine is considered as one of the most widely prevalent illegal narcotics in the world and chronic use of it can alter the feedback processing system of the brain (Lim et al, 2021; R. Smith et al, 2020; N.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations